Gestão ambiental : complexidade sistêmica em bacia hidrográfica - Campos, Yarnel de Oliveira (2010)
The interaction and interdependence of social and physical units occurs in interfaces where domination emerges, which maintains a differentiated transitional power in time and space. In this context environmental management is found and also the organization that is not built purely by the systemic units, but also by actions that connect and give them constructive consistency, which forms, maintains, rules, regulates and reveals the complex unit interacting with its totality, as well as the complex of relations between totality and units. The interaction happens in the combination of actions, relationships and retroactions that occur and builds on a transitional Government system. The systemic complexity is manifest in the conceptions of multiple interactions of natural and social units in different organizations that materialize in a determined territory as dynamic and integrated. Bibliographical research was done in search of a differentiated analysis of environmental management, with a systemic and complex perception in a determined territory with its conceptual limits arbitrated by the assumptions of the conception of basin and its watershed. It is based on the complex approach of Edgar Morin and on the concepts of bureaucracy and power of Max Weber and the concepts of power and learning of Michel Foucault. It is considered that there is a need to broaden the concept of a system made by simple elements, disconnected and integrated in a piecemeal manner, to a multiple relations design that expresses the particular organization of a determined territory and makes possible a complex environmental management with clear and precise limits.